Salt sensitivity and timed drug therapy in arterial hypertension. Enhancing antihypertensive drug efficacy: a controlled randomised trial - V. V. Skibitskiy; V. Yu. Vasil’ev; A. V. Fendrikova (Кубанский научный медицинский вестник, 2021)
Background. An elevated or inadequate sensitivity to salt intake is an important mechanism for maintaining high blood pressure in patients with arterial hypertension. Chronopharmacotherapy comprises an important approach to control arterial hypertension through personalised correction of blood pressure but requires a further proof of efficacy in salt-sensitive hypertensive patients.Objectives. An assessment of six-month dynamics of diurnal and nocturnal peripheral and central blood pressure in salt-sensitive patients with arterial hypertension under chronopharmacotherapy.Methods. A controlled randomised trial included 86 salt-sensitive patients with arterial hypertension. Salt sensitivity was estimated with a Kharchenko’s test. All patients had circadian monitoring of the peripheral and central blood pressure and glomerular filtration rate at baseline and in a six-month follow-up. The patients were randomised into 3 cohorts. Cohort A united patients received perindopril and amlodipine in morning, cohort B — perindopril in morning, amlodipine in evening, cohort C — perindopril in evening, amlodipine in morning. Statistica 12 (StatSoftInc, USA) was used for nonparametric statistical analyses.Results. In six months of chronopharmacotherapy a target arterial pressure was registered in 87.5% patients in cohort A, 96.4 and 96.2% patients in cohorts B and C, respectively. All cohorts exhibited a declining peripheral and central blood pressure over therapy. Cohort A had a greater decline in daytime, and cohorts B and C — both diurnally and nocturnally. Cohorts B and C had more patients with an adequate nocturnal blood pressure decline. Glomerular filtration rate also elevated with perindopril or amlodipine intake before bedtime.Conclusion. The perindopril or amlodipine intake before bedtime in a combined therapy for arterial hypertension provided for a target blood pressure in the overall majority of patients, effectively reduced peripheral and central blood pressure at all time intervals, contributed to optimising the circadian blood pressure profile and increased the glomerular filtration rate.